PENGARUH Trichoderma sp. SEBAGAI AGEN PENINGKATAN KETAHANAN TANAMAN PADI TERHADAP PENYAKIT HAWAR DAUN - Geraldo Sandy; Suskandini Ratih; Radix Suharjo; Hasriadi Mat Akin (Jurnal Agrotek Tropika, 2019)
Rice is one commodity that have an important value for Indonesian people food. But the production of rice plant decreased by attacking of insect and bacterial. The bacterialleaf blight caused by Xanthomonas oryzaepv.oryzae. To avoid the bacterial leaf blight could used Trichoderma sp. suspension to induced resistant in rice plant. This research was conducted at the Laboratory of Plant Disease and Greenhouse of Lampung University. This study was conducted from June 2016 to August 2016.The experiment was conducted in a complete randomized design arranged with two factors, namely varieties of rice and kind isolate of Trichoderma sp.. The results of this study showed that the application of Trichoderma sp. reducing the severity of bacterial leaf blight diseaseand the kind isolate of Trichoderma sp. can increase the length rootand height of rice plant.